Local initiatives in shrinking cities: On Normative Framings and Hidden Aspirations in Scholarly Work - Leona Sandmann; Maria Gunko; Irina Shirobokova; Ria-Maria Adams; Johanna Lilius; Katrin Grossmann (International Journal of Urban and Regional Research, 2024)
Abstract Questions of responsibility for future-making often arise in localities where the withdrawal of capital and state seem to leave tangible voids and a sense of loss. Over the past decade, academic discourse has furthered discussions on the role of civic engagement, local initiatives and their agency under conditions of urban shrinkage. However, scholars (including ourselves) are confronted with their own normative assumptions and aspirations when conceptualizing local initiatives in shrinking cities. Through reviewing the literature on this phenomenon, we identified three main epistemological pitfalls that emerge from the legacies of planning discipline, current neoliberal developments and scholars' own biases. By drawing from our fieldwork experiences, we conclude that local initiatives should be viewed in the plurality of their essences as extremely variegated in form and motivation. We therefore assert the need to disentangle research on local initiatives in shrinking cities from normative aspirations to avoid neoliberal responsibilization, and instead pay attention to the nuances of their aims and practices, achievements and constraints.
Keywords: 330; local initiatives; shrinking cities; governance; civil society; neoliberalization